The river - Paulsen, Gary. (New York : A Yearling Book, 1993)
Transparent overlays depict the plant and animal life found along a river and how rain and winter can change the river.
"Cartwheel books."
Keywords: Stream animals -- Juvenile literature; Rivers -- Juvenile literature; Streamflow -- Juvenile literature; Toy and movable books -- Specimens; Stream animals; Rivers; Toy and movable books